Karyotypic of Golden Little Barb, Puntius brevis Bleeker, 1850 (Pisces: Cyprinidae) from Khon Kaen Province - นิธิกุลวรวงศ์ ณัฎฐา; เครือเนตร วิไลลักษณ์ (KKU Science Journal, 2014)
Karyotype analysis of golden little barb (Puntius brevis Bleeker, 1850) from Khon Kaen province was done in the present study. Mitotic chromosome was prepared directly from kidney of specimens after In vivo colchicines treatment. Conventional staining and Ag-NOR banding techniques were applied to stain the chromosomes accomplished by 20% Giemsa’s and 50% silver nitrate solution, respectively. The results showed that the number of diploid chromosome of golden little barb was 2n = 50, the fundamental numbers (NF) was 62 in both male and female. The types of chromosomes consists of 4 large metacentric, 4 large submetacentric, 2 large acrocentric, 2 medium acrocentric, 26 meduim telocentric and 12 small telocentric chromosomes. Ag-NOR banding techniques demonstrated that there is 1 pair of NOR exists at telomere region on the short arm of acrocentric chromosome pair 6. The karyotype formula of golden little barb is as follows: 2n (50) = Lm4 + Lsm4 + La2 + Ma2 + Mt26 + St12